2006
DOI: 10.1111/j.1574-6968.2006.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli from humans and animals differ in major phenotypical traits and virulence genes

Abstract: Enteroaggregative Escherichia coli (EAEC) is characterized by the expression of the aggregative adherence pattern to cultured epithelial cells. In this study, we determined the phenotypic and genotypic relationships among 86 EAEC strains of human and animal (calves, piglets and horses) feces. Serotypes and the presence of EAEC virulence markers were determined, and these results were associated with ribotyping. Strains harboring aggR (typical EAEC) of human origin were found carrying several of the searched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 34 publications
4
39
0
8
Order By: Relevance
“…Remarkably, individuals with an AA rather than an AT or TT genotype at the Ϫ251 position of the interleukin-8 (IL-8) gene generated greater fecal IL-8 in response to EAEC and were associated with increased infection with EAEC (601). While atypical EAEC has also been identified in calves, piglets, and horses, animals are not an important reservoir of human-pathogenic typical EAEC (602). However, because EAEC isolates are so heterogeneous, it is premature to rule out animal reservoirs for undercharacterized lineages of EAEC.…”
Section: Epidemiologymentioning
confidence: 99%
“…Remarkably, individuals with an AA rather than an AT or TT genotype at the Ϫ251 position of the interleukin-8 (IL-8) gene generated greater fecal IL-8 in response to EAEC and were associated with increased infection with EAEC (601). While atypical EAEC has also been identified in calves, piglets, and horses, animals are not an important reservoir of human-pathogenic typical EAEC (602). However, because EAEC isolates are so heterogeneous, it is premature to rule out animal reservoirs for undercharacterized lineages of EAEC.…”
Section: Epidemiologymentioning
confidence: 99%
“…The pAA plasmid contains several virulence genes, including aggR, aap and aat, but not all EAEC carry the same complement of such genes. While "typical" EAEC strains, such as VT-producing EAEC O104:H4, carry the pAA plasmid or at least the aggR gene, "atypical" strains lack the pAA plasmid and the aggR gene, though they still adhere to the HEp-2 cells in a stacked-brick pattern (Uber et al 2006, Weintraub 2007, EFSA 2011. EAEC appear to have adapted specifically to the human host (Wieler et al 2011): typical EAEC have not been found in animals, and atypical EAEC, although identified in calves, piglets and horses (Uber et al 2006), are not considered zoonotic pathogens (Okhuysen and DuPont 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since this survey used a strain collection that is likely to hold pathogenic, nonpathogenic commensals and possible cross-contaminating isolates, the significance of this finding is unclear. Recently, Uber et al (35) characterized a collection of EAEC strains of human and animal specimens in order to investigate a possible role of animals as reservoir for EAEC human infections. In their work they included some of the EAEC strains used in the present study.…”
Section: Discussionmentioning
confidence: 99%